Sterols from Echinopsis oxygona (Link) zucc. ex Pfeiff - Gonzales, Rhanney L. (Animo Repository, 2020)
Echinopsis oxygona (Link) zucc. ex Pfeiff, commonly known as easter lily cactus and sea urchin cactus, is grown as an ornamental plant in the Philippines. Chemical investigation of the dichloromethane extracts of E. oxygona has led to the isolation of ostreasterol (1), ostreasteryl fatty acid esters (2) and ergosterol peroxide (3) from the flowers and a mixture of β-sitosterol (4) and stigmasterol (5) in about 2:1 ratio from the stems. Compounds 3-5 were reported to exhibit anticancer properties. This is the first report on the chemical constituents of E. oxygona. © 2020 Chemical Publishing Co.. All rights reserved.